2022
DOI: 10.3855/jidc.16635
|View full text |Cite
|
Sign up to set email alerts
|

A clinical case and a review of Mycobacterium fortuitum infections direct diagnosis approach and treatment in a patient with leg fractures

Abstract: Mycobacterium fortuitum infections of the musculoskeletal system are commonly missed, given their rarity and the absence of systemic symptoms. In this study, we isolated the M. fortuitum from the skin sinus tract of a traffic accident patient's right medial knee surgical incision (over the open fracture wound), and confirmed by Morphological analysis, MALDI-TOF MS, 16S rRNA gene sequencing, and mNGS. Then we adjusted the treatment plan and treated the patient with cefoxitin, amikacin, and doxycycline. At three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A study ( Chew et al, 2021 ) of 86 isolates showed that M. fortuitum is resistant to clarithromycin and tobramycin but susceptible to tetracyclines and quinolones. Similarly, a retrospective case series ( Wang J. et al, 2022 ) of 18 patients with cutaneous M. fortuitum complex infections found that five uncomplicated infection cases showed an excellent response to the treatments. One patient received monotherapy of doxycycline for 8 weeks with no recurrence; the other four patients were treated with combined antibiotics, clarithromycin-minocycline, clarithromycin-ciprofloxacin, clarithromycin-TMP-SMX, and ciprofloxacin-TMP/SMX.…”
Section: Main Textmentioning
confidence: 92%
“…A study ( Chew et al, 2021 ) of 86 isolates showed that M. fortuitum is resistant to clarithromycin and tobramycin but susceptible to tetracyclines and quinolones. Similarly, a retrospective case series ( Wang J. et al, 2022 ) of 18 patients with cutaneous M. fortuitum complex infections found that five uncomplicated infection cases showed an excellent response to the treatments. One patient received monotherapy of doxycycline for 8 weeks with no recurrence; the other four patients were treated with combined antibiotics, clarithromycin-minocycline, clarithromycin-ciprofloxacin, clarithromycin-TMP-SMX, and ciprofloxacin-TMP/SMX.…”
Section: Main Textmentioning
confidence: 92%
“…Regardless of in vitro data, in general, there are favorable experiences in including cefoxitin in multidrug regimens to treat infections due to M. fortuitum and M. abscessus. These positive experiences include challenging clinical situations, such as bone and joint infections, pacemaker infection, meningeal infections, renal allograft, and sepsis [86][87][88][89]. It can be used with good success rates in the initial phase of combination treatment (first 4-8 weeks), in the treatment of Mabs disease as a substitute for carbapenems or in intensifying treatment regimens [70,90,91].…”
Section: Cefoxitinmentioning
confidence: 99%